2017
DOI: 10.3389/fmicb.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Modify Plant Microbiomes and Traits by Introducing Beneficial Bacteria at Flowering into Progeny Seeds

Abstract: The microbial component of healthy seeds – the seed microbiome – appears to be inherited between plant generations and can dynamically influence germination, plant performance, and survival. As such, methods to optimize the seed microbiomes of major crops could have far-reaching implications for plant breeding and crop improvement to enhance agricultural food, feed, and fiber production. Here, we describe a new approach to modulate seed microbiomes of elite crop seed embryos and concomitantly design the traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
212
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(222 citation statements)
references
References 52 publications
6
212
0
4
Order By: Relevance
“…However, seed-associated microbial communities are ecologically interesting because they both represent an endpoint and a starting point for community assembly of the plant microbiota (Shade et al 2017). Moreover seedassociated micro-organisms contribute to seed preservation (Chee-Sanford et al 2006) and the release of seeds from dormancy (Goggin et al 2015); they also have been associated with decreased germination rates (Nelson 2004;Munkvold 2009) and enhancement of ear emergence (Mitter et al 2017). Recent diversity surveys of the seed microbiota revealed a high level of variation in microbial assemblages composition (LopezVelasco et al 2013;Links et al 2014;Barret et al 2015;Klaedtke et al 2016;Rezki et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, seed-associated microbial communities are ecologically interesting because they both represent an endpoint and a starting point for community assembly of the plant microbiota (Shade et al 2017). Moreover seedassociated micro-organisms contribute to seed preservation (Chee-Sanford et al 2006) and the release of seeds from dormancy (Goggin et al 2015); they also have been associated with decreased germination rates (Nelson 2004;Munkvold 2009) and enhancement of ear emergence (Mitter et al 2017). Recent diversity surveys of the seed microbiota revealed a high level of variation in microbial assemblages composition (LopezVelasco et al 2013;Links et al 2014;Barret et al 2015;Klaedtke et al 2016;Rezki et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Data presented covers both experimental runs, as the taxonomic breakdown was similar between both runs observed rhizosphere bacterial communities of maize grown on sterile sand and non-sterile soils all contained the same dominant operational taxonomical units (OTUs), indicating the seed as a common source of inoculum (Johnston-Monje, Lundberg, Lazarovits, Reis, & Raizada, 2016). While two taxa may not seem meaningful, Mitter et al (2017) observed that by introducing a single bacterial endophyte to the flowers of parent wheat plants, vertical transmission of the endophyte into the seed was successfully achieved. The vertical transmission of this single bacterial endophyte also translated into benefits in faster spike onset in the greenhouse and ears per square meter in the field compared with seeds without the endophyte present (Mitter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While two taxa may not seem meaningful, Mitter et al (2017) observed that by introducing a single bacterial endophyte to the flowers of parent wheat plants, vertical transmission of the endophyte into the seed was successfully achieved. The vertical transmission of this single bacterial endophyte also translated into benefits in faster spike onset in the greenhouse and ears per square meter in the field compared with seeds without the endophyte present (Mitter et al, 2017). Even small contributions to the microbiome from seed bacterial communities can result in increased plant health.…”
Section: Discussionmentioning
confidence: 99%
“…S. marcescens , a common plant-associated bacterium, also exhibits various antibiotic resistances and opportunistic traits 29 . Less is known to this end for the identified Paraburkholderia and Rouxiella species, especially for P. phytofirmans , which is a promising plant growth promoting agent 30 . Interestingly, plants in general and Sphagnum in particular constitute reservoirs for plant growth promoting bacteria with antifungal and antibacterial activity 31 , while simultaneously hosting species known as opportunistic human pathogens 16,32 .…”
Section: Discussionmentioning
confidence: 99%